Integrasi Pembelajaran Bahasa Arab melalui Lomba Poster Edukatif di MA Ma'arif NU Kencong - Asni Furoidah (INAIFAS Press, 2026)
Arabic language learning at the Madrasah Aliyah level often faces challenges in the form of low interest and motivation of students due to teaching methods that tend to be conventional and theoretical. This research is based on the need for learning media innovations that are able to integrate language skills with visual creativity to create a more enjoyable and applicable learning atmosphere. This study aims to analyze the integration of Arabic language learning through educational poster competitions at MA Ma'arif NU Kencong and measure the effectiveness of poster competitions in improving mastery of mufradat (vocabulary). The service method used is Community Service with an Asset Based Community Development (ABCD) approach. The stages of service include socialization, workshops on making Arabic poster content, conducting competitions, and evaluating the results. The results of the service show that this integration has succeeded in increasing students' enthusiasm and facilitating the understanding of language concepts through creative visualization, while strengthening the identity of Arabic literacy in the school environment. This competition also develops 21st century skills such as critical thinking, creativity, collaboration and digital literacy.